2018
DOI: 10.3389/fmicb.2018.00888
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Bifidobacterial Strains Against Toxigenic Clostridium difficile

Abstract: Probiotics might offer an attractive alternative to prevent and control Clostridium difficile (C. difficile) infection (CDI). Limited information is available on the ability of commercially used bifidobacterial strains to inhibit C. difficile. This study examined the anti-clostridial effects of Bifidobacterium longum JDM301, a widely used commercial probiotic strain in China, in vitro and in vivo. In vitro evaluation revealed a significant reduction in C. difficile counts when JDM301 was co-cultured with C. di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 60 publications
2
44
0
Order By: Relevance
“…Many studies have also demonstrated that Lactobacillus and Bifidobacterium are associated with colonization resistance against C. difficile (Lawley et al, 2012;Petrof et al, 2013;Valdes-Varela et al, 2016;Martz et al, 2017;De Wolfe et al, 2018;Vedantam et al, 2018). Bifidobacterium longum JDM301, a widely used commercial probiotic strain, can inhibit C. difficile growth and degrade TcdA and TcdB, and the author further proved that the exertion of inhibition of B. longum is dependent on an acidic pH (Wei et al, 2018). We speculate that Lactobacilli with acid-and bile salt-tolerance which ensured to reach the intestine, could provide an acidic microenvironment in which Bifidobacteria can maximize the suppression of C. difficile.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many studies have also demonstrated that Lactobacillus and Bifidobacterium are associated with colonization resistance against C. difficile (Lawley et al, 2012;Petrof et al, 2013;Valdes-Varela et al, 2016;Martz et al, 2017;De Wolfe et al, 2018;Vedantam et al, 2018). Bifidobacterium longum JDM301, a widely used commercial probiotic strain, can inhibit C. difficile growth and degrade TcdA and TcdB, and the author further proved that the exertion of inhibition of B. longum is dependent on an acidic pH (Wei et al, 2018). We speculate that Lactobacilli with acid-and bile salt-tolerance which ensured to reach the intestine, could provide an acidic microenvironment in which Bifidobacteria can maximize the suppression of C. difficile.…”
Section: Introductionmentioning
confidence: 95%
“…A histological graded scoring system was used to assess pathological tissue inflammation as follows: 0, normal; 1, inflammatory cells increase in lamina propria; 2, inflammatory cells increase in submucosa; 3, plenty of inflammatory cell mass. Stained sections were examined and evaluated blindly by a certified pathologist (Chen et al, 2008;Wei et al, 2018).…”
Section: Histopathological Analysismentioning
confidence: 99%
“…Bifidobacteria are believed to restrain cancer development by various mechanisms including oligosaccharide fermentation and biotransformation and by increasing the integrity of the intestinal barrier. Lactic fermentation is also suggested to have an antiproliferative effect on colorectal cancer cells, and lactic bacteria such as Bifidobacterium were reported to exhibit preventive effects against colon, bladder, liver, breast, and gastric cancer [108]. Moreover, the Lactobacilli, together with the Bifidobacteria, produce acetate and lactate.…”
Section: Liver Cirrhosismentioning
confidence: 99%
“…B. longum JDM 301 is a widely used commercial probiotic strain in China ( Wei et al, 2010 ). Our previous study demonstrated that B. longum JDM 301 can prevent Clostridium difficile infection (CDI) in mice ( Wei et al, 2018 ). In the present study, we used B. longum JDM 301 as a model probiotic to test factors that could potentially influence the therapeutic effect of probiotics in experimental colitis.…”
Section: Introductionmentioning
confidence: 99%